The Effect of the Hypnoteaching Method on Student Achievement in Fiqh Lessons - Agusalim Agusalim; Jihan Jihan; Muh. Safar; Agustinus Lewerissa; Agus Mukholid (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Education is a change in the behavior of students for the better. In education teachers have an important role in the progress of education. The teacher plays a major role in achieving educational goals. Teachers must be able to develop the potential of students optimally. In the process of optimally developing the potential of students, a teacher should be able to convey learning material appropriately and well. One of the things that must be mastered in learning is the learning method. One of the learning methods is the hypoteaching method. This study aims to see the effect of using the hypoteaching method in learning jurisprudence in schools on student learning outcomes. The research method that the author uses is a quantitative research method by distributing questionnaires to teachers and students at schools related to the use of the hypoteaching method in learning Fiqh. From the results of the research that the authors did, the use of the hypoteaching method in learning greatly influenced student learning outcomes. The hypoteaching method is often used by teachers in learning. The hypoteaching method makes students more enthusiastic in learning which increases student achievement.